2019
DOI: 10.21240/mpaed/35/2019.10.15.x
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Media literacy as intergenerational project: skills, norms, and mediation

Abstract: The extensive research literature on media literacy is reflected by diverse theoretical conceptions, assumptions, and conclusions. Nevertheless, the considerations of numerous scholars in this «patchwork of ideas» (Potter 2010, 676) revolve around the importance of critical thinking and the interplay of different generations in the acquisition of media literacy.Many scholars argue that critical thinking is a key qualification for the reflection of possible risks and a media use oriented towards opportunities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…With older children, parents often do not even know what the children share about themselves on the Internet, and with younger children, the parents themselves share large amounts of data (Aswathy Prakash, 2019). These conclusions are also agreed by (Riesmeyer et al, 2019), who studied several dozen families in depth. They found that parents are often more protective of their privacy and personal data than of their children's data.…”
Section: Resultssupporting
confidence: 73%
“…With older children, parents often do not even know what the children share about themselves on the Internet, and with younger children, the parents themselves share large amounts of data (Aswathy Prakash, 2019). These conclusions are also agreed by (Riesmeyer et al, 2019), who studied several dozen families in depth. They found that parents are often more protective of their privacy and personal data than of their children's data.…”
Section: Resultssupporting
confidence: 73%